Effect of some insecticides and fungicides on nitrogen fixation and nodulation of a seed treatment of beans (Phaseolus vulgaris) - Ruschel, Alaides Puppin; Costa, Walter Francisco da (Pesquisa Agropecuaria Brasileira, 2024)
In the present greenhouse experiment the effects on nitrogen fixation and nodulation of a seed treatment of beans (Phaseolus vulgaris) with Gesarol 33, Carunchol 50, Malagran, Phostoxin, Arasan 75, Uspulun, Neantina, Semesan are studied. The treated seeds were inoculated with Rhizobium phaseoli and planted in a sandy soil, with pH 4.5. At the time of blooming the plants were harvested and determined the number of nodules, the dry weight, nitrogen percentage and total nitrogen. The following conclusions could be made: 1. No effect of any of the insecticides used in this experiment could be observed on Rhizobium or nitrogen fixation. 2. The fungicides Semesan and Neatina reduced considerably the number of nodules and the nitrogen fixation. Caution should be taken when these fungicides are applied together with inoculants. The injurious effect probably can be attributed to the high mercury content of these substances.